Marjatta
Dec 13, 2020

answers: 1

Register to add an answer

The time for answering the question is over

Answer:

x = 3

y = 2

2x + y = 8 ------> 1.

x - 2y = - 1

x = - 1 + 2y ------> 2.

Substitute 2 in 1,

2 ( - 1 + 2y ) + y = 8

- 2 + 4y + y = 8

- 2 + 5y = 8

5y = 8 + 2

5y = 10

y = 10 / 5

y = 2

Substitute y = 2 in 2.

x = - 1 + 2 ( 2 )

= - 1 + 4

x = 3

352

Niran

Dec 13, 2020

For answers need to register.

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions